Mortality rate and factors associated with mortality of carbapenem-resistant Enterobacteriaceae infection - Apichart So-ngern; Naphol Osaithai; Atibordee Meesing; Worawat Chumpangern (AboutScience Srl, 2023)
Background: Carbapenem-resistant Enterobacteriaceae (CRE) is a serious pathogen with high mortality. Recognition of factors associated with mortality and treating these modifiable factors are crucial to reducing mortality. Objective: To determine the 30-day mortality and factors associated with a 30-day mortality of CRE infection. Methods: A retrospective cohort study was conducted between January 1, 2015, and December 31, 2019. All patients diagnosed with CRE infection aged ≥18 years were included. Multivariate logistic regression was used for evaluating the factors associated with 30-day mortality and presented as adjusted odds ratio (aOR) with 95% confidence interval (CI). Result: One hundred and ninety-four patients were enrolled. The 30-day mortality occurred in 75 patients (38.7%). The common antibiotic regimen was monotherapy and combination of carbapenem, colistin, amikacin, tigecycline, and fosfomycin. CRE isolates were susceptible to tigecycline (93.8%), colistin (91.8%), fosfomycin (89.2%), and amikacin (89.2%). The independent factors associated with 30-day mortality were an increasing simplified acute physiology (SAP) II score (aOR 1.11, 95% CI 1.05-1.16, p < 0.001), sepsis at time of CRE infection diagnosis (aOR 7.93, 95% CI 2.21-28.51, p = 0.002), pneumonia (aOR 4.48, 95% CI 1.61-12.44, p = 0.004), monotherapy (aOR 4.69, 95% CI 1.71-12.85, p = 0.003), and improper empiric antibiotic (aOR 5.13, 95% CI 1.83-14.40, p = 0.002). Conclusion: The overall 30-day mortality of CRE infection was high. The factors associated with mortality were an increasing SAP II score, sepsis at time of CRE infection diagnosis, pneumonia, monotherapy, and improper empiric antibiotic. The study suggested that proper empiric antibiotic and combination antibiotics might reduce mortality from CRE infection.